(untitled) (Development Engineering Conferences Center Articles Database, 2025)
This study introduces the Quick Financial Capacity Assessment (QFCA) methodology, designed to evaluate the financial stability of suppliers efficiently and rapidly. By focusing on four key financial metrics—Operating Profit (OP), Special Profit (SP), Income Tax (T), and Insurance Costs (Ins)—the methodology enables swift and scalable evaluations [1]. The proposed formula provides a streamlined process for calculating financial capacity, making it ideal for initial supplier assessments. Although the calculations offer valuable insights for decision-making, they serve as preliminary tools, requiring further in-depth analysis for comprehensive evaluations. This methodology prioritizes speed and efficiency, ensuring timely supplier evaluations in large-scale procurement processes [1,2].